Regularizing effect in singular semilinear problems - Carmona, José; Martínez Aparicio, Antonio J.; Martínez-Aparicio, Pedro J.; Martínez-Teruel, Miguel (Mathematical Modelling and Analysis, 2023)
We analyze how different relations in the lower order terms lead to the same regularizing effect on singular problems whose model is in Ω, u = 0 on ∂Ω, where Ω is a bounded open set of is a nonnegative function in L1(Ω) and g(x,s) is a Carathéodory function. In a framework where no solution is expected, we prove its existence (regularizing effect) whenever the datum f interacts conveniently either with the boundary of the domain or with the lower order term.